2012
DOI: 10.1245/s10434-012-2514-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Locoregional Recurrence in Patients With False-Negative Frozen Section or Close Margins of Retroareolar Specimen in Nipple-Sparing Mastectomy

Abstract: Despite a high reliability of frozen section, there is still a minority of false-negative results. Nevertheless, the LRR is considerably low. This fact suggests the possibility of preservation of the NAC after discussion with the patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 42 publications
0
27
0
3
Order By: Relevance
“…[1][2][3][4] However, more recently, many groups have begun offering the approach to patients with larger tumors and no longer require preoperative magnetic resonance imaging (MRI) to document distance from the NAC, but instead just ensure that examination shows no clinical involvement of the NAC. [5][6][7][8] One group of patients now offered TSSM at some centers are those with locally advanced breast cancer, [9][10][11] although outcomes analysis of these patients after TSSM is limited and often grouped within larger studies that include earlier-stage and prophylactic patients.…”
mentioning
confidence: 99%
“…[1][2][3][4] However, more recently, many groups have begun offering the approach to patients with larger tumors and no longer require preoperative magnetic resonance imaging (MRI) to document distance from the NAC, but instead just ensure that examination shows no clinical involvement of the NAC. [5][6][7][8] One group of patients now offered TSSM at some centers are those with locally advanced breast cancer, [9][10][11] although outcomes analysis of these patients after TSSM is limited and often grouped within larger studies that include earlier-stage and prophylactic patients.…”
mentioning
confidence: 99%
“…Characteristics such as tumor size, histologic type, staging, location, human epidermal growth factor receptor 2 (HER2) amplification, lymphovascular invasion, intraductal spread, and clinical appearance of the NAC (including the presence of nipple discharge) all have been shown to affect tumor involvement of the NAC. 12 Pathologic studies of patients undergoing NSSM or TSSM have reported a wide range of NAC involvement risk ranging from 2.5 to 14 %. 2,10,11,[13][14][15] Few data exist on the optimal way to manage TSSM cases with NAC involvement or on the oncologic outcomes for these patients, particularly in highrisk populations.…”
mentioning
confidence: 99%
“…10,11 Many studies have recommended that NSM only be performed in patients with peripheral tumors located no closer than 5 cm to the NAC. 2 Several studies have described NAC necrosis after NSM.…”
Section: Discussionmentioning
confidence: 99%